Menyuarakan Keadilan Allah dalam Narasi Hari Tuhan: Studi Struktur Orasi Amos 5:7-20 - Yanti, Maria Evvy; Lasut, Wahyu (STT Iman Jakarta, 2023)
The Book of Amos contains a collection of prophetic orations consisting of a collection of prophetic traditions and compilation documents. There are various interpretations, especially in interpreting the Day of the Lord based on the prophet's oration in Amos 5:7-20. For example, there are those who interpret that the Day of the Lord is a time for the statement of the Most Holy God in the midst of human behavior that violates His will. Some interpret it as a day of punishment for the disbelievers and bringing glory to God's people. Some see it as the destruction of the Israelites and other nations when the day of the Lord arrives. There are also those who understand the Day of the Lord to be a terrible and terrible event because God is angry. The purpose of writing this article is to find the theology about the Day of the Lord in Amos 5:7-20. The method used is analysis of the literary structure of orations. The result of this research is that the Day of the Lord is God's justice which is practiced through upholding truth and humanization which provides prosperity for the people. Abstrak Kitab Amos berisi kumpulan orasi nabi yang terdiri dari koleksi tradisi nabi dan dokumen-dokumen kompilasinya. Terdapat beragam penafsiran, khususnya dalam menafsirkan Hari Tuhan berdasarkan orasi nabi pada Amos 5:7-20 Misalnya, ada yang menafsirkan bahwa Hari Tuhan adalah waktu pernyataan Allah yang Maha Suci di tengah perilaku manusia yang melanggar kehendak-Nya. Ada yang menafsirkan sebagai hari penghukuman bagi orang-orang kafir dan membawa kejayaan kepada umat Allah. Ada yang memandangnya sebagai kebinasaan bangsa Israel dan bangsa-bangsa lain ketika tiba hari Tuhan. Ada juga yang memahami Hari Tuhan menjadi peristiwa yang mengerikan dan dahsyat karena Tuhan murka. Tujuan penulisan artikel ini ialah untuk menemukan teologi tentang Hari Tuhan dalam Amos 5:7-20. Metode yang digunakan ialah analisis struktur sastra orasi. Hasil penelitian ini ialah bahwa Hari Tuhan sebagai keadilan Allah yang dipraktikkan melalui penegakkan kebenaran dan humanisasi yang memberikan kesejahteraan bagi umat.